Design, synthesis and biological activity of N4-phenylsubstituted-7H-pyrrolo[2,3-d]pyrimidin-4-amines as dual inhibitors of aurora kinase A and epidermal growth factor receptor kinase - Sonali Kurup; Bradley McAllister; Pavlina Liskova; Trusha Mistry; Anthony Fanizza; Dan Stanford; Jolanta Slawska; Ulrich Keller; Alexander Hoellein (Taylor & Francis Group, 2018)
Simultaneous inhibition of multiple kinases has been suggested to provide synergistic effects on inhibition of tumour growth and resistance. This study describes the design, synthesis and evaluation of 18 compounds incorporating a pyrrolo[2,3-d]pyrimidine scaffold for dual inhibition of epidermal growth factor receptor kinase (EGFR) and aurora kinase A (AURKA). Compounds 1-18 of this study demonstrate nanomolar inhibition of EGFR and micromolar inhibition of AURKA. Compounds 1-18 allow for a structure-activity relationships (SAR) analysis of the 4-anilino moiety for dual EGFR and AURKA inhibition. Compound 6, a 4-methoxyphenylpyrrolo[2,3-d]pyrimidin-4-amine, demonstrates single-digit micromolar inhibition of both AURKA and EGFR and provides evidence of a single molecule with dual activity against EGFR and AURKA. Compound 2, the most potent inhibitor of EGFR and AURKA from this series, has been further evaluated in four different squamous cell head and neck cancer cell lines for downstream effects resulting from AURKA and EGFR inhibition.